2005
DOI: 10.1200/jco.2005.02.8589
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Protein Expression Profiling Identifies CDK6 As Novel Independent Prognostic Marker in Medulloblastoma

Abstract: We identified CDK6 as a novel molecular marker that can be determined by immunohistochemistry on routinely processed tissue specimens and may facilitate the prognostic assessment of medulloblastoma patients. Furthermore, increased protein-levels of PPM1D and CDK6 may link the TP53 and RB1 tumor suppressor pathways to medulloblastoma pathomechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
172
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 200 publications
(185 citation statements)
references
References 56 publications
11
172
0
2
Order By: Relevance
“…PPM1D (also known as PP2Cd and WIP1) is a member of the PPM family (Fiscella et al, 1997), which is characterized by Mg 2 þ /Mn 2 þ -dependent activity and relative insensitivity to okadaic acid. PPM1D is encoded by a putative oncogene that is amplified in multiple cancer types Li et al, 2002;Hirasawa et al, 2003;Saito-Ohara et al, 2003;Mendrzyk et al, 2005;Shreeram et al, 2006), including 11-16% of human primary breast cancers, most of which express wild-type P53 Li et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…PPM1D (also known as PP2Cd and WIP1) is a member of the PPM family (Fiscella et al, 1997), which is characterized by Mg 2 þ /Mn 2 þ -dependent activity and relative insensitivity to okadaic acid. PPM1D is encoded by a putative oncogene that is amplified in multiple cancer types Li et al, 2002;Hirasawa et al, 2003;Saito-Ohara et al, 2003;Mendrzyk et al, 2005;Shreeram et al, 2006), including 11-16% of human primary breast cancers, most of which express wild-type P53 Li et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 MiR-124 is the most abundant neuronal miRNA, playing a critical role in neurogenesis and neuronal differentiation. [28][29][30] Expression of miR-124a was shown to be significantly reduced in medulloblastomas compared to normal controls in this study, a trend similar to that observed in adult brain tumors.…”
Section: Mirnas In Medulloblastomamentioning
confidence: 99%
“…[35][36][37] CDK6 is overexpressed in lymphoma, leukemia, glioma, glioblastoma, medulloblastoma, and cancers of squamous cells, salivary gland, bladder, pancreas and prostate. [38][39][40][41][42][43][44][45][46][47][48][49][50] In human prostate cancer cells, CDK6 has also been shown to bind androgen receptor and stimulate its activity in a kinase activity independent manner. 46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…48,54,71 Medulloblastoma comprises multiple and distinct molecular entities whose clinical and genetic differences likely require separate therapeutic strategies. Four principal sub-groups of medulloblastoma have been identified: those with Wnt pathway mutations, Sonic Hedgehog pathway mutations, and those termed Groups 3 and 4.…”
Section: Introductionmentioning
confidence: 99%